2022
DOI: 10.1088/1748-9326/ac5d99
|View full text |Cite
|
Sign up to set email alerts
|

Subnational assessment of threats to Indian biodiversity and habitat restoration opportunities

Abstract: The active involvement of subnational authorities, cities and local governments has been identified as one of the enabling conditions to implement the Convention on Biological Diversity’s (CBD) post-2020 Global Biodiversity Framework and progress towards United Nations’ Sustainable Development Goal #15 (Life on Land). However, there has not been any systematic application of any biodiversity metric at the subnational level to identify where the main responsibilities and opportunities lie within a country. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The main driver behind global land use change has been our food system. A majority of Earth’s ice-free land is currently used for the purpose of agriculture (crops and livestock production), and ongoing agricultural expansion has been the predominant driver behind ongoing deforestation, resulting in habitat loss, fragmentation, and degradation for native biodiversity and consequently causing their population decline and eventual extinction. , …”
Section: Crop Intensification and Land Savings Debatementioning
confidence: 99%
“…The main driver behind global land use change has been our food system. A majority of Earth’s ice-free land is currently used for the purpose of agriculture (crops and livestock production), and ongoing agricultural expansion has been the predominant driver behind ongoing deforestation, resulting in habitat loss, fragmentation, and degradation for native biodiversity and consequently causing their population decline and eventual extinction. , …”
Section: Crop Intensification and Land Savings Debatementioning
confidence: 99%
“…Several studies have shown that per serving of cereals, vegetables, and fruits require less cropland rather than livestock products and thus transitioning from animal-based to plantbased diet can reduce the demand for natural land clearing (Aleksandrowicz et al, 2016;Clark et al, 2019;Chaudhary et al, 2022). Others have shown that a shift toward the recommended healthy pattern (SDG 2 and 3) in affluent countries would co-benefit SDG 15 due to a lower land demand than current average footprints Ridoutt et al, 2020).…”
Section: Dietary Change and Sdg15-life On Landmentioning
confidence: 99%
“…It is based on the scope (proportion of the global population impacted), severity (rate of decline driven by the threat within its scope) and timing (past, ongoing, or future) of threats. Mair et al (2021) used the STAR metric to identify opportunities for threat abatement and restoration in a global context, and Chaudhary et al (2022) and Mair et al (2023) used it at a national scale. Strassburg et al (2020) used the Red List data to calculate ‘Area of Habitat’ to identify priority areas for conservation.…”
Section: Biodiversity Considerations In Existing Toolsmentioning
confidence: 99%